Research Questions, Concepts & Operationalisation - sddss, ssddsd (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2013)
People frequently confuse the terms hypothesis and theory. They are very different. A hypothesis is very mucha tentative set of statements based on observations â or even hunches and guesses â but there is no body oftested evidence to support them. When does a hypothesis become a theory? A